Islamization of Knowledge and It's Grounding: Appraisal and Alternative - Hanafi, Sari (Universitas Islam Internasional Indonesia, 2022)
In recent decades, there has been much discussion on 'Islamically-grounding' the social sciences, which some researchers have described as being traditionally 'Western' in nature. This debate among Muslims flourished in the early nineties, taking place in books, articles and doctoral theses. As a sociologist, I have no qualms about using the terms 'Islamic', 'Arab', or 'Lebanese' to describe some social sciences and for some of the concepts and theories of these sciences to be inspired by the Islamic heritage and these societies. However, through a content analysis of articles, books and masters and PHD theses that adopt this orientation, as well as through interviews with some of the proponents of the Islamization of Knowledge (IoK) or Islamic grounding (ta’sil) of knowledge, I show that adding a geographical or religious adjective to the social sciences creates real problems. This paper describes and presents a synthesis of this literature, analyzes some of its problems and ponders whether the project to 'Islamize' knowledge is truly necessary or instead serves as a sort of identity politics. Based on this analysis, this paper suggests a new approach that I call 'separation, connection and pluralistic praxis' as an alternative to IoK and similar projects.